Analysis of Trade Trends in Global Non-Precious Metal Markets - Zeleniy, O.; Lyashenko, V.; Shapran, O. (IJAMR, 2022)
International trade occupies one of the key places in the system of economic relations, the development of various sectors of the economy and society. This is achieved through the organization and functioning of various types and types of markets t hat allow us to implement and maintain the necessary economic relations. This, ultimately, determines the feasibility of conducting ongoing research aimed at analyzing trade trends in world markets. Such an analysis can be carried out both from the point of view of the development of market relations in general, and taking into account the specifics of the functioning of individual market segments. Among the many segments of the world market, we single out the base metals market. The base metal market is a part of the commodity market where primary goods are traded. This makes this market special and attracts close attention. We consider the statistical characteristics of futures for various types of non-precious metals; we present the dynamics of such quotes. To analyze the mutual influence of individual quotes on futures, wavelet coherence estimates are used in the work. The paper presents a number of graphs and diagrams that help to understand the logic of the study, the reliability of the results.
Keywords: world market; wavelet coherence